2006
DOI: 10.1111/j.1748-7692.2006.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Diving Limit Brain Size in Cetaceans?

Abstract: We test the longstanding hypothesis, known as the dive constraint hypothesis, that the oxygenation demands of diving pose a constraint on aquatic mammal brain size.Using a sample of 23 cetacean species we examine the relationship among six different measures of relative brain size, body size, and maximum diving duration. Unlike previous tests we include body size as a covariate and perform independent contrast analyses to control for phylogeny. We show that diving does not limit brain size in cetaceans and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…increased blood volume and myoglobin levels in muscle tissue) commonly observed in diving marine mammals (Worthy & Hickie, 1986). Moreover, Marino et al. (2006) found that dive constraints do not influence relative brain size investment in cetaceans (whales, dolphins and porpoises) and argued that large muscle mass associated with increased body mass primarily influences the duration of cetacean dives.…”
Section: Discussionmentioning
confidence: 99%
“…increased blood volume and myoglobin levels in muscle tissue) commonly observed in diving marine mammals (Worthy & Hickie, 1986). Moreover, Marino et al. (2006) found that dive constraints do not influence relative brain size investment in cetaceans (whales, dolphins and porpoises) and argued that large muscle mass associated with increased body mass primarily influences the duration of cetacean dives.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an extensive fossil record, surprisingly little is known about the tempo of the neocete radiation. It has, however, been suggested to have been 'explosive', driven by the evolution of key characters relating to sociality and brain size (Marino et al 2006), echolocation and baleen as key innovations in the odontocetes and mysticetes, respectively (Fordyce 1992), or radiation into vacant niches following the extinction of archaeocete lineages in the Early Oligocene (Fordyce & de Muizon 2001;Fordyce 2003;Clementz et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cetaceans possess a number of adaptations that aid diving, including increased myoglobin levels (i.e., an oxygen-storing and iron-carrying protein found in the muscles of all mammals); increased blood volume; and a higher concentration of hemoglobin than in terrestrial mammals [120]. However, dive limits are also dictated by rates of oxygen consumption, which is of particular relevance when discussing a very oxygen-sensitive organ like the brain.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, those that dive regularly, e.g., sperm whales, have the highest concentrations. Indeed, sperm whales are better than any other animal at staying underwater for long periods without having to take air (e.g., they can stay underwater for approximately 73 min at a time [120]). Diving mammals have higher concentrations of this protein, but according to Mirceta et al [131] they also exhibit an adaptation: the surface of this oxygen-binding protein possesses a net surface charge causing it to repel itself more strongly, thus enabling deep diving animals to pack their myoglobin into even higher concentrations (proteins tend to stick together at high concentrations impairing their function).…”
Section: Terrestrial Mammals Lacking Internal Granular Layer IV In Thmentioning
confidence: 99%